Workshop Pembuatan Website Menggunakan Wix Untuk Meningkatkan Keterampilan Teknologi Siswa SMP 15 Tangerang Selatan - Muhammad Daffa Katianda; Ahmad Daerobi Baihaqi; Dava Arie Pratama; Ilyas Tri Hardono; Muhammad Rifqi Fudhoil; Rio Novrianto; Syakib Binnur; Zainal Abidhin; Maulana Ardhiansyah (CV. Multi Kreasi Media, 2026)
The development of information technology demands increased digital literacy from elementary and secondary education levels. Websites, as a digital medium, play a role in conveying information, promotion, and communication. However, website creation skills among junior high school students are still limited (Mz & Thahir, 2020). This community service activity aims to improve students' technological skills through a website creation workshop using the Wix platform at SMPN 15 South Tangerang. The implementation method included surveys and interviews to map initial conditions, literature studies as a theoretical foundation, Focus Group Discussions (FGDs) to develop training plans, and hands-on practice in drag-and-drop website creation using Wix (Afiyanti, n.d.). The results of the activity showed that students were able to understand basic website concepts and produce simple, functional, and creative websites. Wix is ​​considered effective as a learning medium because it makes it easy for beginners to build websites without programming skills, thus supporting the improvement of students' digital literacy (Andreansyah & Dharma, 2022; Indonesia et al., 2022).